Modern views in the clinic and diagnosis of bruxism. (Review) (Texas Journal of Medical Science, 2022)
The functional states of the masticatory muscles are interrelated with the general states of the muscular systems and the whole organism as a whole. An increase in muscle-strength contractions during pathological tooth abrasion violates the compensatory-protective abilities of the dental-maxillary system, while the functional balance is disturbed, phenomena and features of active bruxism appear, all this is a key mechanism for the development of pathology